Antecedents of Patient Loyalty to Private Hospital in Makassar City, Indonesia: A Service Quality Approach - Hasanudin, Damis (2015)
The research aims to find out: (1) the influence of hospital service quality on the hospital image, patients value, satisfaction, and loyalty; (2) the influence of private hospital image in Makassar on patient loyalty, value, and satisfaction; (3) the influence of patient's value on patient's satisfaction and loyalty; (4) the influence patient's satisfaction on patient's loyalty. The samples in this research were patients in private hospitals in Makassar city: Ibnu Sina, Stella Maris, Grestelina, and Faisal Islamic hospitals. There were 300 respondents taken using accidental sampling and stratified random sampling technique, and the data were analysed using Structural Equation Model (SEM). The research result reveals that: (1) service quality has significantly positive influence to hospital image; (2) service quality has significantly positive influence to patient's value; (3) service quality has insignificantly positive influence to patient's satisfaction; (4) service quality has significantly positive influence to patient's loyalty; (5) hospital image has significant influence to patient's value; (6) hospital image has significant influence to patient's satisfaction; (7) hospital image has insignificant influence to patient's loyalty; (8) patient's value has significantly positive influence to patient's satisfaction; (9) patient's value has insignificantly positive influence to patient's loyalty; (10) patient's satisfaction has significantly positive influence to patient's loyalty; (11) service quality has significantly indirect positive influence to the patient's value through hospital image; (12) service quality has significantly indirect positive influence to patient's satisfaction through hospital image and patient's value; (13) service quality has significantly indirect positive influence to patient's loyalty through hospital image, patient's value, and satisfaction; (14) hospital image has significantly indirect positive influence to patient's satisfaction through patient's value; (15) hospital image has significantly indirect positive influence to patient's loyalty through patient's satisfaction; (16) patient's value has significantly indirect positive influence to patient's loyalty through patient's satisfaction.